Meta-Analysis Using NGS Data: The Veillonella Species in Dental Caries - Naile Dame-Teixeira; Naile Dame-Teixeira; Ana Karolina Almeida de Lima; Thuy Do; Cristine Miron Stefani (Frontiers Media S.A., 2021)
Objectives: In light of recent technological advances in Next-generation sequencing (NGS) and the accumulation of large, publicly available oral microbiome datasets, the need for meta-analysing data on caries microbiome is becoming feasible and essential. A consensus on the identification of enriched organisms in cariogenic dysbiotic biofilms would be reached. For example, members of the Veillonella genus have been detected in caries biofilms, and may have an underestimated contribution to the dysbiotic process. Hence, we aimed to determine the abundance of Veillonella species in dental caries in studies using NGS data.Materials and Methods: Analysis was performed according to the Preferred Reporting Items for Systematic Review and Meta-Analysis (registered at PROSPERO: CRD42020204150). Studies investigating microbial composition in saliva, dental biofilm, or carious dentin were included. Six databases and grey literature were searched. Two independent reviewers selected the papers and assessed the methodological quality.Results: Searches retrieved 1,323 titles, from which 38 studies were included in a qualitative synthesis, comprising a total of 1,374 caries and 745 caries-free individuals. Most studies analysed 16S rRNA amplicons, and only 5 studies used shotgun metagenomics and metatranscriptomics. A geographical bias was observed. The methodological quality was downrated in 81.5% of the studies due to the lack of criteria for defining cases and standard criteria used for measurement of the condition in a reliable way. Six studies on early childhood caries (ECC) were meta-analysed, confirming a significant enrichment of Veillonella spp. in caries-associated biofilms (but not saliva) when compared to caries-free controls [mean difference: 2.22 (0.54-3.90); p = 0.01].Conclusions:Veillonella spp. is more abundant in individuals suffering with ECC when compared to caries-free controls (very low evidence certainty), and should be considered for further studies to observe their metabolism in dental caries. There is an urgent need for a consensus in methodologies used to allow for more rigorous comparison between NGS studies, particularly including clinical data and details of caries diagnosis, as they are currently scarce. Inconsistent reporting on the NGS data affected the cross-study comparison and the biological connexions of the relative abundances on caries microbiome.